If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(7 + -2x) = 65 (7 * 5 + -2x * 5) = 65 (35 + -10x) = 65 Solving 35 + -10x = 65 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + -10x = 65 + -35 Combine like terms: 35 + -35 = 0 0 + -10x = 65 + -35 -10x = 65 + -35 Combine like terms: 65 + -35 = 30 -10x = 30 Divide each side by '-10'. x = -3 Simplifying x = -3
| 2(x-3)=8+3x | | 11x+25=7x+1 | | 9x+7=4x-4 | | 5(y+3)=18-6y | | 5y-3x^3=127 | | 6x-1=15*-55 | | 4(4.5+2.5)-2y=5 | | 19x-6=6(x+3)-10 | | 2xy+4x-y=4 | | 4(9x+2)=153 | | P=-2b-3t-2t+b | | 46x-45x=1 | | 2w+30=60-x | | T=3a-4b+2a+b | | 3x-11=ax+6 | | x^2/3-11x/6-1=0 | | 10t-3=24 | | a/9=15 | | X-7x+6=30 | | 0=x+4-9x | | 2.6=-5.2(3.4+x) | | 0.1x=1.4 | | 34=-0.4(x+22) | | -0.26=logx | | -4(-5-b)= | | 3(x-9)=6(x+3) | | sinx=-0.95 | | 10x+15x-8+3=-2x+3-8 | | 7p-8=-3p+6 | | 2=4y-2y-6 | | 6e-15=15 | | x+37=3x+9 |